Hubungan Antara Status Gizi Dengan Siklus Menstruasi Pada Siswi MAN 1 Lamongan - Nurul Maulid Dya; Sri Adiningsih (Amerta Nutrition, 2019)
Background: Puberty is a period that occurs in adolescence. Puberty in young women is characterized by the occurrence of menarche. Adolescent is an age group that is prone to menstrual disorders, one of which is an abnormal menstrual cycle. Abnormal menstrual cycles can be predictors of reproductive health problems. One of the factors that causes an abnormal menstrual cycle is nutritional status.Objective: This study aimed to analyze the relationship between nutritional status and menstrual cycles in female students of Islamic Senior High School Lamongan.Method: This cross-sectional designed study was conducted on the 10th and 11th-grade students of Islamic Senior High School 1, Lamongan. The determination of the sample was done by simple random sampling to choose 83 students. Data related to the menstrual cycle was obtained by interview using a questionnaire. Nutrition status data was obtained by measuring height, weight. Nutritional status was classified by using the BMI/U z-score table values for girls aged 5-18 years from the Indonesian Ministry of Health. Data analyzed using the Spearman correlation test with α = 0.05.Results: The results showed that respondents with normal nutritional status (66.3%) mostly had normal menstrual cycles (62.7%). Respondents with obesity tend to experience abnormal menstrual cycles (71.4%). Based on the results of statistical tests, it was known that there was a relationship between nutritional status with the menstrual cycle (p = 0.036).Conclusions: There was a relationship between nutritional statuses with the female students’ menstrual cycle of Islamic Senior High School 1, Lamongan ABSTRAKLatar Belakang: Salah satu fase dalam pekembangan manusia adalah masa remaja. Masa pubertas merupakan masa yang terjadi pada masa remaja. Pubertas pada remaja putri ditandai dengan terjadinya menarche. Remaja perempuan merupakan kelompok usia yang rentan mengalami gangguan menstruasi seperti siklus menstruasi yang tidak normal. Salah satu faktor yang menyebabkan siklus menstruasi yang tidak normal yaitu status gizi.Tujuan: penelitian ini bertujuan untuk menganalisis hubungan antara status gizi dengan siklus menstruasi siswi MAN 1 Lamongan.Metode: Analitik observasional merupakan jenis dari penelitian ini dan cross sectional merupakan desain pada penelitian ini. Populasi pada penelitian ini merupakan siswi kelas X dan XI Madrasah Aliyah Negeri 1 Lamongan (MAN 1 Lamongan). Penentuan sampel dilakukan dengan simple random sampling dan didapatkan besar sampel adalah 83 siswi. Data terkait siklus menstruasi didapatkan dengan wawancara menggunakan kuisioner. Data status gizi didapatkan dengan melakukan pengukuran tinggi badan, berat badan. Status gizi diklasifikasikan dengan menggunakan nilai tabel z-score IMT/U untuk anak perempuan usia 5-18 tahun dari kemenkes RI. Analisis data menggunakan uji korelasi spearman dengan α = 0,05.Hasil: Hasil penelitian menunjukkan bahwa responden dengan status gizi normal (66,3%) sebagian besar memiliki siklus menstruasi yang normal (62,7%). Responden dengan status gizi yang tidak normal cenderung mengalami siklus menstruasi yang tidak normal. Berdasarkan hasil uji statistik, diketahui bahwa terdapat hubungan antara status gizi dengan siklus menstruasi dengan nilai p = 0,036.Kesimpulan: Terdapat hubungan antara status gizi dengan siklus menstruasi siswi MAN 1 Lamongan.